CSDC2, a cold shock domain RNA-binding protein in decidualization - Vallejo, Griselda (2018)
RNA-binding proteins (RBPs) have been described for cancer cell progression and differentiation, although there is still much to learn about their mechanisms. Here, using in vivo decidualization as a model, we describe the role of RBP cold shock domain containing C2 (CSDC2) in the endometrium. Csdc2 messenger RNA expression was differentially regulated depending on time and areas of decidua development, with the most variation in antimesometrium (AM) and, to a lesser degree, in the junctional zone (JZ). Immunohistochemistry of CSDC2 showed a preferentially cytoplasmic localization at AM and JZ, and nuclear localization in underneath myometrium and mesometrium (M). Cytoplasmic localization coincided with differentiated, DESMIN-marked areas, while nuclear localization coincides with proliferative zones. Uterine suppression of CSDC2 through intrauterine-injected-specific small interfering RNA (siRNA) led to abnormal decidualization in early pregnancy, with more extended antimesometrial area and with poor M development if compared with control siRNA-injected animals. These results suggest that CSDC2 could be a regulator during decidua development.